Kemampuan Berpikir Kritis Siswa Melalui Pembelajaran Berbasis Lingkungan untuk Studi Ekosistem Sungai - Fema Anggriani; Bhakti Karyadi; Aceng Ruyani (University of Bengkulu, 2019)
ABSTRACT[Capacity of student critical thinking through learning base on ecosystem study of water river]. South Bengkulu one of regencies in Bengkulu Province, located west in of the Bukit Barisan Mountains range which has a height of 600-1200 meters above sea level. South Bengkulu has a lot natural wealth that can be utilized as a medium of learning. This research aims to measure the ability of critical thinking and process skill student of class VII MTN 2 south Bengkulu by utilizing environment-based teaching materials. This research uses observation data collection techniques and test (pre test and post test ) Assessment of process skill conducted on two learning activities that is indoor and out door learning activities. Performance of process skill from student of class VII MTsN 2 South Bengkulu including into the category excellent and good while student critical thinking skills classically including into the critical categoryKeywords: student critical thinking skills; environment-based teaching materials’ pre test and post test.(Received November 19, 2018; Accepted April 15, 2019; Published June 18, 2019) ABSTRAKBengkulu Selatan adalah salah satu kabupaten di Provinsi Bengkulu terletak di sebelah barat pegunungan Bukit Barisan di mana ketinggian pegunungan tersebut rata-rata 600-1200 m diatas permukaan laut (dpl) yang mempunyai banyak kekayaan alam yang dapat dimanfaatkan sebagai media pembelajaran. Penelitian ini bertujuan 1) Mengukur kemampuan berfikir kritis siswa dan ketrampilan proses siswa kelas VII MTsN 2 Bengkulu Selatan dengan memanfaatkan bahan ajar berbasis lingkungan. Penelitian ini menggunakan teknik pengumpulan data observasi dan tes (pre test dan Post test). Penilaian keterampilan proses ini dilakukan pada dua kegiatan pembelajaran indoor dan kegiatan pembelajaran outdoor. Kemampuan kinerja keterampilan proses siswa kelas VII MTsN 2 bengkulu Selatan termasuk kedalam kategori sangat baik dan Baik dan kemampuan berpikir kritis siswa secara klasikal termasuk kedalam kategori Kritis.Kata Kunci: Kemampuan berpikir kritis siswa, bahan ajar berbasis lingkungan, Pre test dan post test.